Mirabegron-Induced Smooth Muscle Relaxation: Review of the Suggested Mechanisms - Rahma Almallah; Hani Almukhtar (University of Mosul, 2023)
Background: Mirabegron operates through a distinct mechanism compared to antimuscarinic agents. Its activation of β3-adrenoceptors results in the relaxation of the bladder during the filling phase of micturition. The activation of β3-adrenoceptors, which are connected to Gs-proteins, is hypothesized to be the mechanism of mirabegron-induced smooth muscle relaxation. This coupling stimulates adenylyl cyclase, leading to an elevation of intracellular levels of cyclic adenosine monophosphate (cAMP). However, in rat and human corpus cavernosum, mirabegron induces relaxation through distinct mechanisms independently through the nitric oxide/cyclic guanosine monophosphate (NO-cGMP) pathway. Consequently, the precise mechanism by which mirabegron enhances relaxation is still not fully known. Aim: The main goal is to delve deeper into the complex mechanisms by which mirabegron causes smooth muscle relaxation in many tissues. Conclusion: Mirabegron and similar β3-adrenoceptor agonists hold promise for treating not only overactive bladder but also a range of other conditions including heart failure and metabolic disorders.